Digital death mortality and beyond in the online age - Moreman, Christopher M. 1974- (Praeger, 2014)
"This fascinating work explores the meaning of death in the digital age, showing readers the new ways digital technology allows humans to approach, prepare for, and handle their ultimate destiny"..
Includes bibliographical references and index
Keywords: SOCIAL SCIENCE / Death & Dying; SOCIAL SCIENCE / Future Studies; Gesellschaft; Death -- Social aspects; Information technology -- Social aspects; Internet -- Social aspects; Sozialer Wandel; Sterben; Social Media; Tod; Alltagsbewusstsein; Aufsatzsammlung